Teacher career calling reduces burnout: The mediation effects of work engagement and psychological capital - Zhao, Xuan; Wu, Kejia; Sun, Binghai; Li, Weijian (Frontiers in Psychology, 2022)
Burnout is a serious problem in the teaching profession in Chinese primary and secondary schools. Research suggests that career calling could be regarded as a protective factor against burnout; however, the mediating mechanism underlying this relationship remains to be explored. The purpose of this study was to test the mediating roles of work engagement and teachers’ psychological capital. A total of 3,300 elementary and secondary school teachers completed a self-report questionnaire. SPSS 21.0 was used to conduct data analyses. Results showed that the relationship between career calling and burnout was mediated by work engagement and teacher psychological capital parallelly and sequentially. These findings provide insights for preventing burnout among teacher groups.